2021
DOI: 10.1016/j.celrep.2021.109253
|View full text |Cite
|
Sign up to set email alerts
|

Tumor vessel co-option probed by single-cell analysis

Abstract: Highlights d Single-cell RNA-seq of 31,964 cells from a lung-vessel cooption tumor model d The transcriptome of co-opted and healthy vascular cells is largely similar d Matrix-remodeling macrophages might assist invasive cancer cells to co-opt vessels d An M1-like macrophage subtype may keep vascular cells quiescent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 156 publications
(213 reference statements)
1
81
0
Order By: Relevance
“…As widely discussed across this review, LRG1 orchestrates pathological blood vessel formation [ 29 ] by enhancing proliferation, migration and invasion of endothelial cells [ 35 ], as well as the expression of several pro-angiogenic factors including TGFβ, VEGFA and Angiopoietin-1, in both endothelial [ 35 , 190 ] and cancer cells [ 197 ]. A recent study on tumour vessel co-option, where tumours grow around existing vessels rather than through neoangiogenesis, revealed that Lrg1 was one of the few genes significantly upregulated in endothelial cells, as both endothelial and pericyte transcriptomes were otherwise largely indistinguishable from those of normal vessels [ 201 ]. The effects of LRG1 on the cancer vasculature are therefore most likely inevitable and supportive of tumour progression.…”
Section: Reviewmentioning
confidence: 99%
“…As widely discussed across this review, LRG1 orchestrates pathological blood vessel formation [ 29 ] by enhancing proliferation, migration and invasion of endothelial cells [ 35 ], as well as the expression of several pro-angiogenic factors including TGFβ, VEGFA and Angiopoietin-1, in both endothelial [ 35 , 190 ] and cancer cells [ 197 ]. A recent study on tumour vessel co-option, where tumours grow around existing vessels rather than through neoangiogenesis, revealed that Lrg1 was one of the few genes significantly upregulated in endothelial cells, as both endothelial and pericyte transcriptomes were otherwise largely indistinguishable from those of normal vessels [ 201 ]. The effects of LRG1 on the cancer vasculature are therefore most likely inevitable and supportive of tumour progression.…”
Section: Reviewmentioning
confidence: 99%
“…Neutrophils have been recently shown to contribute to tumor vascularization, also through non-angiogenic mechanisms, vessel co-option, and vascular mimicry [106,107]. High neutrophil expression of LOXL4 in colorectal cancer liver metastases (mainly via vessel co-option) has been proposed to be the key factor responsible for the resistance against antiangiogenic therapy [108].…”
Section: Neutrophils and Tumor Angiogenesismentioning
confidence: 99%
“…Some other evidence suggests that tumour cells can compress and destabilise the pre-existing vasculature, activating a host defence mechanism which initiates an apoptotic response leading to regression of co-opted vessels and perfusion impairment [83]. This ultimately leads to hypoxia and necrosis triggering further neovascularisation, so a combination of neovascularisation and co-option can exist together [84].…”
Section: Vessel Co-optionmentioning
confidence: 99%
“…Vessel co-option has been suggested as a mechanism of resistance to anti-angiogenic therapy [83]. Preclinical models of pulmonary metastases display vessel co-option after anti-VEGF therapy [84]. On the other hand, it was shown that in human patients with colorectal cancer liver metastasis, vessel co-option appears in those with poor response to the anti-angiogenic drug bevacizumab [85].…”
Section: Vessel Co-optionmentioning
confidence: 99%